Quality Assurance of IoT based Systems using Analytic Hierarchy Process (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things (IoT) has attracted wide attention in various industrial and customer applications. In 2021 there will be approximately 50 billion devices connected to IoT across the globe. With the increasing globe, the question arises to focus on quality assurance of the IoT applications. The performance of the IoT-based systems is the directly dependent quality of hardware and software. Quality assurance (SQA) is a crucial factor for maintaining the quality of service of IoT-based applications. The existing quality models mainly focus on the software aspects of the applications. This paper presents an Analytic Hierarchy Process (AHP) for the quality evaluation of IoT applications which comprises software as well as hardware. An agriculture field monitoring system application based on Wireless Sensor Network (WSN) and IOT is considered to evaluate the proposed quality model. We present simple Fuzzy logic algorithm for the agriculture field monitoring. The performance of the proposed quality model is evaluated against various quality attributes such as functional suitability, compatibility, maintainability, usability, performance efficiency, security, reliability, and portability. The proposed SQA approach gives a consistency index and overall quality measure of 0.061 and 0.7564 respectively. It has shown significant improvement over the previous state of arts such as Grey and IA-QM SQA approaches.